Analisis Kesetaraan Dalam Kemitraan Pada Agribisnis Hortikultura - Erfit Erfit (Jurnal Embrio, 2012)
The aims of Study are to look at the aspect of equality based on any existing partnerships in agri-horticulture in particular for commodity vegetables. This study uses multy case study that combines case studies and surveys. The results showed that the aspect of equality in the partnership between farmers traditionally seen relationships with partners or traders is relatively equal. This situation can be seen from the relative amount of authority on the part of farmers to take some decisions on the run partnership which includes: commodity pricing, determination of the quality of commodities produced the timing of planting, harvest timing, and land management. Unlike the case of contract farming premises equality aspect shows the relative absence of equality which shows a very high dominance in the enterprise. It can be seen dominant company in making decisions related to the course of the partnership.